Investigation of possibility of identification sex marker in beluga (Huso huso) and Persian sturgeon (Acipenser persicus) by using of molecular techniques - Yarmohammadi, Mahtab; Pourkazemi, M.; Hassanzadeh Saber, M.; Chakmehdooz, F.; Baradaran Novairi, Sh.; Fashkhami, M.R.; Mardi, M. (Iranian Fisheries Science Research Institute, 2009)
Due to high maturation age in sturgeons and lack of morphologic differences between male and female even in brood stocks, sex determination is difficult in these species. In this research with using of AFLP approach and 100 primer combinations, male and female genomic DNA of 20 individuals in Persian sturgeon (Acipenser persicus) and beluga (Huso huso) were investigated. Ligation was carried out with using of MseI and EcoRI, and then adapters were ligated with using of T4 DNA Ligase. Fragments amplification was done through two steps PCR and electrophoresis on denature poly acrylamid and stained by silver staining. Data derived from banding patterns were scored as o (absence) and 1 (Presence). A set of 100 (Eco+3 and Mse+4) primer combinations in A. persicus and H. huso yielded approximately a total of 3771 and 3779 scorable bands, respectively of which 30% in A. persicus and 29.6% in H. huso were polymorphic. The fragments ranged from 50 to 600 bp without revealing any sex specific markers. So we used cDNA-AFLP approach in order to analysis of gene expression in 8 female and 8 male Persian sturgeon gonads. Results revealed two cDNA markers in female gonad (TDF1, TDF2) and they verified with RT-PCR in male and female gonads cDNA. But unfortunately they didn’t verify in genomic DNA. According to this research results and previous researches, it seems that sturgeons may have not sex chromosomes or the methods were used couldn’t determine them.